Determination of the Critical Period of Crop-weed Competition: Impact on Weed Dynamics, Growth and Yield of Greengram (Vigna radiata L.) - Karnavat, M. P.; Hatti, Veeresh; Pradhan, P. C.; Kumar, Vikash; Singh, A. K.; Prajapati, J. A. (International Journal of Economic Plants, 2026)
A field experiment was conducted during kharif (July–September) 2024 at Agronomy Instructional Farm, Department of Agronomy, C. P. College of Agriculture, Sardarkrushinagar Dantiwada Agricultural University, Sardarkrushinagar, Banaskantha (North Gujarat Agro-climatic Zone of Gujarat) to assess the critical period of crop-weed competition in greengram (Vigna radiata L.) under North Gujarat condition on loamy sand soil. The experiment was conducted under randomized block design with eight treatments and three replications. Among the different treatments weed free upto harvest treatment recorded significantly higher seed and stover yield (1344 and 3247 kg ha-1, respectively) and was found at par with weed free upto 45 DAS (1235 and 3125 kg ha-1, respectively), weed free upto 30 DAS (1155 and 2956 kg ha-1, respectively) and weedy upto 15 DAS (1122 and 2816 kg ha-1, respectively) as compared to weedy upto harvest (636 and 1462 kg ha-1, respectively) owing to significantly lower dry weight of grasses, sedges, broad leaf and total weeds at 15, 30, 45 DAS and at harvest with higher weed control efficiency and lower weed index values. Furthermore, weed free upto harvest recorded higher net returns followed by weed free upto 45, 30 DAS and weedy upto 15 DAS as compared to weedy upto harvest.